Death-Domain-Receptor 3 Deletion Normalizes Inflammatory Gene Expression and Prevents Ileitis in Experimental Crohn's Disease. Issue 1 (5th October 2018) - Buttó, Ludovica F; Jia, Li-Guo; Arseneau, Kristen O; Tamagawa, Hiroshi; Rodriguez-Palacios, Alex; Li, Zhaodong; De Salvo, Carlo; Pizarro, Theresa T; Bamias, Giorgos; Cominelli, Fabio
Abstract: Background: TNF-like cytokine 1A (TL1A) and its functional receptor, death-domain-receptor-3 (DR3), are multifunctional mediators of effector and regulatory immunity. We aimed to evaluate the functional role and therapeutic potential of TL1A/DR3 signaling in Crohn's disease–like ileitis. Methods: Ileitis-prone SAMP1/YitFc (SAMP) and TNF ΔARE/+ mice were rendered deficient for DR3 or TL1A by microsatellite marker-assisted backcrossing. Pathological and immunological characteristics were compared between control and knockout mice, and mucosal immunophenotype was analyzed by Nanostring microarray assay. The therapeutic effect of pharmacological TL1A neutralization was also investigated. Results: DR3 deficiency was associated with restoration of a homeostatic mucosal immunostat in SAMP mice through the regulation of several pro- and anti-inflammatory genes. This led to suppression of effector immunity, amelioration of ileitis severity, and compromised ability of either unfractionated CD4 + or CD4 + CD45RB hi mucosal lymphocytes to transfer ileitis to severe combined immunodeficient mice recipients. TNF-driven ileitis was also prevented in TNF ΔARE/+ xDR3 -/- mice, in association with decreased expression of the pro-inflammatory cytokines TNF and IFN-γ. In contrast to DR3, TL1A was dispensable for the development of ileitis although it affected the kinetics of inflammation, as TNF ΔARE/+ xTL1A -/- demonstrated delayed onset of inflammation, whereas administration of a neutralizing, anti-TL1A antibody ameliorated early but not late TNFΔARE/+ ileitis. Conclusion: We found a prominent pro-inflammatory role of DR3 in chronic ileitis, which is only partially mediated via interaction with TL1A, raising the possibility for additional DR3 ligands. Death-domain-receptor-3 appears to be a master regulator of mucosal homeostasis and inflammation and may represent a candidate therapeutic target for chronic inflammatory conditions of the bowel.